Penetapan Titik Kendali Kritis (TKK) pada Proses Produksi Bakso di PT XYZ - Lesmana, Angga; Uzwatania, Fina; Ginantaka, Aditia (Food Scientia : Journal of Food Science and Technology, 2024)
Critical control point (CCP) is one of  seven basic principles in Hazard Analysis Critical Control Points (HACCP) as a step to determine important points that must be controlled in the production process. Determination of CCP is the key in reducing or eliminating identified hazards or reducing the impact of hazards to an acceptable level. PT XYZ is one of the companies developing the segmentation of ready-to-eat frozen food processing, namely meatballs. The need for the implementation of CCP at PT XYZ ensures that the meatballs provided to consumers are healthy and safe. The purpose of research is to identify, analyze and control the hazards that may occur in the process production of meatballs. The method that used in this research is through a qualitative approach in the form of process analysis and Critical Control Points at the step of the meatball production process, as well as establishing corrective actions for monitoring procedures at the process stages. The results showed that the process that became the critical control point (CCP) was the boiling process in the form of heavy metals, insects and foreign matter hazards. The corrective action  is use a metal detector machine to anticipate heavy metal contamination and re-monitoring personal hygiene, use of PPE, and equipment cleanliness.